2006
DOI: 10.1088/0957-0233/17/6/001
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the electric field radiated by electrostatic discharges

Abstract: The electrostatic discharge (ESD) between charged metal objects produces electromagnetic (EM) fields having broad-band frequency spectra over a microwave region, which cause serious EM interference (EMI) to high-tech information equipment. For this kind of ESD fields, focussing on EM fields due to the spark discharge between metal spheres in free space, we previously demonstrated that the presence of metal spheres enhances the field level according to their sizes. For the EMI due to the above ESD, however, its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2007
2007
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…So far, the exact sensors that will be used to measure the E/M field have not been determined. From the measurements of the E/M field, listed previously for different arrangements, when the coaxial adapter was on an insulating material [39] or in the center of a metal surface [37,38] it was concluded that both the values and the waveforms of the generated fields differ depending on the experimental devices and the sensors used.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…So far, the exact sensors that will be used to measure the E/M field have not been determined. From the measurements of the E/M field, listed previously for different arrangements, when the coaxial adapter was on an insulating material [39] or in the center of a metal surface [37,38] it was concluded that both the values and the waveforms of the generated fields differ depending on the experimental devices and the sensors used.…”
Section: Introductionmentioning
confidence: 88%
“…During the verification of these generators and for contact discharges, Fotis et al [37,38] measured the electric and magnetic fields radiated by commercial ESD generators at various distances from the discharge point and at various directions in the near field. The same E/M field sensors were used by Pommerenke et al [12] for modeling electrostatic discharge.…”
Section: Measurement Setups and Instrumentation For The Measurement O...mentioning
confidence: 99%
See 1 more Smart Citation
“…Electric field measurements, on the other hand, are considerably more challenging, and there is a lack of experimental data on how the electric field distributes around the PT and varies with time [30]. Methods such as capacitive probes [43][44][45], electrostatic fluxmeters [46], and electrooptic probes based on Pockels effect [47][48][49][50] are not optimal because they inevitably disturb the electric field distribution. While optical emission spectroscopy based on the application of polarization-dependent Stark splitting and shifting can leave the field undisturbed [51][52][53], the emission-based method is only sensitive to specific species (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, at high frequencies-usually beyond 30 MHz-it is a common practice to consider radiated coupling leading over conducted paths, yet on second thoughts some sort of conducted energy must be taken into account at least in the last leg of the coupling path when EMI reaches the internal components of the equipment via cables. The fuzzy border between the solely radiated and conducted nature of EMI is well outlined in [2] for electrostatic discharges, while in [3] the authors have already shown the presence of electromagnetic fields radiated from cables used in conducted immunity tests as the port of entry of a portion of EMI into the EUT. To assess EMC characteristics, specific harmonized standards have been issued by European normalization institutions: compliance with the tests contained therein ensures compliance with the EMC directive of the European Union [4].…”
Section: Introductionmentioning
confidence: 99%